Integrating One Health into High School teaching: A Practical Guide for Teachers - Korma, B; Tesfaye, B; Wondim, E; Abuna, F; Kebede, Y; Tadesse, Y; Mor, Siobhan M.; Mutua, Florence K.; Richards, S; Kaba, M (International Livestock Research Institute, 2024)
In recent years, the world has faced unprecedented challenges. The emergence of zoonotic diseases, increasing food insecurity, growing antimicrobial resistance, and the threat of global pandemics have underscored the fragility of ecosystem health at large and the wellbeing of humankind. These issues are further compounded by climate change, globalization, intensive agricultural practices, population growth, and widespread antimicrobial use in food production. Against this backdrop, the One Health approach stands out as a critical strategy, aiming to address health challenges at the intersection of human, animal, and environmental health.